Cultural Governance in Österreich: Eine interpretative Policy-Analyse zu kulturpolitischen Entscheidungsprozessen in Linz und Graz - Schad, Anke Simone (transcript, 2019)
Cultural governance is weak in Austria. The book offers inspiration and practical hints on what good governance in the cultural sector could ideally look like.